Mucoepidermoid Carcinoma in a 33-Year-Old White Man. Issue 4 (20th November 2015) - Behring, Christina M.; Lazzari, Michael A.
Abstract : Patient Demographics: A 33-year-old white man. Chief Complaint: Longstanding bump on the roof of the mouth. Treatment: The patient was referred to an oral maxillofacial surgeon for a pathology consultation. The patient had been experiencing pain on both sides of his jaw, but the oral mass was not painful (Image 1 ). Medical History: The patient has no history of smoking, is slightly overweight with a body mass index of 26.5, and has no systemic or chronic medical conditions. Examination Findings: On initial examination by the oral surgeon, the vital signs of the patient were normal. An indurated lesion was noted on the left hard palate of the patient. Suspecting a benign lesion or possible carcinoma/neoplasm, the oral surgeon scheduled and performed an excisional biopsy (Image 2 ). The mass was sent for pathological processing. Postoperative Care: This included a diet of soft foods, with daily rinsing using 0.12% chlorhexidine gluconate, with a follow-up appointment made for 2 weeks later. Principal Laboratory Findings: Figure 1 ; Image 3 ; Image 4